AI- Driven Gamified Wellness System As A Strategic Differentiation In Smart Boutique Hotels - Dwi Novita Cahyaningtyas Permatasari; Innocentius Dwijaya Lestari; Vivi; Dinar Sukma Pramesti; Bryant Kim An (Journal of Business on Hospitality and Tourism, 2026)
The rapid integration of artificial intelligence (AI) in hospitality has shifted hotels from accommodation providers to holistic experience facilitators. At the same time, wellness tourism continues to grow globally, yet most hotel wellness services remain passive and non-personalized. This study aims to examine how the AI-driven gamified wellness system, ATHERIA ASCLEPIUS, was developed in this study to enhance guest experience and create strategic differentiation for boutique hotels. Using a qualitative case-study approach, data were collected through prototype testing, semi-structured interviews with hotel managers, and user simulations. The findings indicate that AI-based personalization combined with gamification increases guest engagement, perceived value, and potential length of stay. The study contributes to smart hospitality literature by introducing a non-medical, preventive AI wellness framework integrated into hotel ecosystems and offers practical implications for boutique hotel operators seeking technology-driven differentiation.